Apoptotic blebs from Leishmania major-infected macrophages as a new approach for cutaneous leishmaniasis vaccination. (October 2020) - Faridnia, Roghiyeh; Kalani, Hamed; Hezarjaribi, Hajar Ziaei; Denny, Paul W.; Rafie, Alireza; Fakhar, Mahdi; Virgilio, Stela
Abstract: We focused on apoptotic blebs from Leishmania major -infected macrophages as a vaccine for cutaneous leishmaniasis. Apoptosis was induced in L. major -infected J774A.1 cells in order to prepare apoptotic blebs. Test groups of BALB/c mice were immunized with these at doses of 1 × 10 6, 5 × 10 6 or 1 × 10 7 blebs. An immunization control group received Leishmania lysate antigens. The results showed that as the number of apoptotic bodies increased, the lymphocyte proliferation index increased, and this was proportional to IFN-γ level in the test groups. Additionally, the difference of IFN-γ, IL-4, IFN-γ/IL-4 ratio, or total IgG ( p  < 0.0001) in all groups was statistically significant compared to the negative control group. The highest IFN-γ (514.0 ± 40.92 pg/mL) and IFN-γ/IL-4 ratio (2.94 ± 0.22) were observed in the group that received 1 × 10 7 apoptotic blebs. The highest levels of IL-4 (244.6 ± 38.8 pg/mL) and total IgG (5626 ± 377 μg/mL) were observed in the immunization control group. Reflecting these data, no lesions were observed in any of the groups vaccinated with apoptotic blebs after 12 weeks. In summary, the use of apoptotic blebs from L. major- infected macrophages is protective against the challenge with L. major in this animal model. Highlights: No lesions were observed in the groups vaccinated with apoptotic blebs from Leishmania major -infected macrophages. Apoptotic blebs contain a wide variety of the parasite antigens, stimulating immune responses like whole killed parasite. The highest IFN-γ and IFN-γ/IL-4 ratio were observed in the group that received 1 × 10 7 apoptotic blebs. The immunization with apoptotic blebs protected mice from cutaneous swelling against Leishmania major challenge.